HOẠT ĐỘNG KARST CỦA KHỐI ĐÁ VÔI PHONG NHA - KẺ BÀNG DƯỚI GÓC ĐỘ THUỶ ĐỊA HOÁ - Thiên, Đỗ Quang; Yến, Nguyễn Thị Ngọc; Minh, Vũ Cao (Vietnam Journal of Earth Sciences, 2012)
Karst activity of Phong Nha - Ke Bang’s Limestone under Hydro - Geochemical viewpoint Based on the analysis results of 5 water samples taken from limestone of Phong Nha - Ke Bang area in Januany 2009, the authors has used the method of comparation between active product and dissalved limestone production and the method of lacking content in saturation of [Ca2+], [CO3 2-] anions in water for assessment of Karst activity intensity. The calculated results from different methods show that Karst activity of reseach limestone taking place with intensity from weak to very weak. On this basis, assessment the Karst denudated intensity through dissolved limestone thickness for one year is 31.12×10-3 mm. In comparison with others limestone blocks on the world, the Karst denudated intensity of Phong Nha – Ke Bang’s limestone block is weak.